2020
DOI: 10.3390/fermentation6030085
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Halogenated Compounds on the Anaerobic Digestion of Macroalgae

Abstract: The urgent need to replace fossil fuels has seen macroalgae advancing as a potential feedstock for anaerobic digestion. The natural methane productivity (dry weight per hectare) of seaweeds is greater than in many terrestrial plant systems. As part of their defence systems, seaweeds, unlike terrestrial plants, produce a range of halogenated secondary metabolites, especially chlorinated and brominated compounds. Some orders of brown seaweeds also accumulate iodine, up to 1.2% of their dry weight. Fluorine remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 172 publications
0
9
0
Order By: Relevance
“…Bromophenols are molecules composed of one to five phenol groups, bound to one or more bromine [ 174 ]. Bromophenols are produced by seaweed as part of their chemical defence system to protect them from herbivores [ 175 ], oxidation, bacteria, and fungi [ 176 , 177 ]. Tri-bromophenols are the most common isomers found in seaweed, followed by di- and mono- bromophenols [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bromophenols are molecules composed of one to five phenol groups, bound to one or more bromine [ 174 ]. Bromophenols are produced by seaweed as part of their chemical defence system to protect them from herbivores [ 175 ], oxidation, bacteria, and fungi [ 176 , 177 ]. Tri-bromophenols are the most common isomers found in seaweed, followed by di- and mono- bromophenols [ 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibition of methanogen lowers the pH, leading to the accumulation of volatile fatty acids and the subsequent suppression of the anaerobic digestion process. As part of their chemical defence systems, seaweed also produces a variety of halogenated secondary metabolites, particularly chlorinated and brominated compounds (Nielsen et al 2020 ). In 90% of red seaweed and 7% of green seaweed, chlorinated and brominated metabolites predominate, whereas iodine-containing metabolites predominate in brown seaweeds (Nielsen et al 2020 ).…”
Section: Seaweed As a Feedstock For The Anaerobic Digestion Processmentioning
confidence: 99%
“…As part of their chemical defence systems, seaweed also produces a variety of halogenated secondary metabolites, particularly chlorinated and brominated compounds (Nielsen et al 2020 ). In 90% of red seaweed and 7% of green seaweed, chlorinated and brominated metabolites predominate, whereas iodine-containing metabolites predominate in brown seaweeds (Nielsen et al 2020 ). Some brown seaweed types can build up to 1.2% of the iodine per seaweed dry weight.…”
Section: Seaweed As a Feedstock For The Anaerobic Digestion Processmentioning
confidence: 99%
“…A multitude of scientific research indicated that ocean warming has caused ecological impacts on various marine flora and fauna species across the globe, with a range of species marching away from their native homes in search of cooler climes [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. With heatwaves sweeping through oceans twice as much as they did in the early 1990s, many biodiversity hotspots around the world are on the verge of imminent collapse.…”
Section: At a Glance: Key Defence Strategies Of Marine Macroalgae Aga...mentioning
confidence: 99%
“…Over the past decade, considerable attention has been devoted to understanding the interactions between algal halogenated compound production and the environment, which includes global and anthropogenic climate changes [ 124 , 131 ]. Given that macroalgae produce a range of halogenated secondary metabolites, particularly chlorinated and brominated compounds that are predominant in red (90%) and green (7%) macroalgae, many studies have been conducted using these macroalgae to aid biosorption of pollutants in both industry and agriculture [ 124 , 132 ]. It is worth noting that halogenation of macroalgal components is involved in chemical defence mechanisms because halogenated metabolites are often associated with antibacterial, antifungal, antibacterial, and antioxidant properties [ 132 , 133 ].…”
Section: At a Glance: Key Defence Strategies Of Marine Macroalgae Aga...mentioning
confidence: 99%